Organization and information in Simondon's theory of individuation. Issue 1 (1st January 2017) - Rodriguez, Pablo; Blanco, Javier
ABSTRACT: This article explores the notions of organization and information in Gilbert Simondon's theory of individuation. It confronts these notions with ideas from cybernetics and especially Alan Turing's work. The 'universal machine' opens new ways of understanding the relations between humans and machines, and highlights an impasse in Simondon's theory. These concepts act as precursors to post-structuralist philosophy and Gilles Deleuze's oeuvre.